1986
DOI: 10.1002/ajpa.1330690413
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status, sex, age, and ethnicity as determinants of body fat distribution for Guatemalan children

Abstract: The distribution of subcutaneous fat at the triceps and subscapular skinfold sites is described for four groups of children living in Guatemala. These groups are high socioeconomic status (SES) children of Ladino (mixed Spanish and Indian) ancestry, high SES children of European ancestry, low SES Ladino children, and very low SES Indian children. The method of Healy and Tanner (1981) is used, employing regression and principal components analysis of log transformed skinfold values to divide "fatness" into two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
17
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 16 publications
4
17
1
Order By: Relevance
“…These findings appear to contrast with those reported by Spender and co-workers (1988) on children with cerebral palsy and those reported by Bogin and co-workers on Guatemalan children of lower socioeconomic status (Bogin and MacVean 1981a,b;Bogin and Sullivan, 1986). These workers have found that the triceps site shows differential depletion when compared to the subscapular site, associated with chronic malnutrition in their samples.…”
contrasting
confidence: 75%
“…These findings appear to contrast with those reported by Spender and co-workers (1988) on children with cerebral palsy and those reported by Bogin and co-workers on Guatemalan children of lower socioeconomic status (Bogin and MacVean 1981a,b;Bogin and Sullivan, 1986). These workers have found that the triceps site shows differential depletion when compared to the subscapular site, associated with chronic malnutrition in their samples.…”
contrasting
confidence: 75%
“…The higher amount of central fat in the lower SES sample appears also in samples in Guatemala (Bogin and MacVean, 1981;Bogin and Sullivan, 1986) and India (Johnston et al, 1995). In the present sample, however, the differences are evident only in girls and, in contrast, in a sample from San Antonio, Texas (Malina, 1996), only Mexican American males of higher social class revealed a more android pattern (according to waist:hip ratio).…”
Section: Socioeconomic Differencesmentioning
confidence: 86%
“…Research on twins (Selby et al, 1990) suggests that fat distribution is determined more by genetic factors than by habits (physical exercise being considered the main variable for defining habits and lifestyle). However, the varied environments defined by socioeconomic status (SES) may also have a relationship with fat distribution (Bogin and Sullivan, 1986). Among an English population of Caucasian origin, children of employees had more fat at the triceps site than children of parents with other professions; further, the number of persons in the household had a positive correlation with the amount of fat at the triceps site (Rona and Chinn, 1987).…”
mentioning
confidence: 99%
“…This method of separating size and shape is preferable to the residual methods often used in growth research (e.g., Bogin and Sullivan, 1986) because it removes isometric size (for a full discussion of ratio and residual methods, see Jungers et al, 1995). The shape variables are therefore not necessarily uncorrelated with size, as required by residual methods.…”
Section: Methodsmentioning
confidence: 98%